2022
DOI: 10.1002/hpja.620
|View full text |Cite
|
Sign up to set email alerts
|

A nurse‐led Asthma Care Team transitioning patients from hospital to home improves asthma control: A pilot study exploring an alternative model of care

Abstract: Introduction Recurrent asthma admissions are frequent in our patients at a tertiary Australian hospital and are commonly related to poor health literacy and medication adherence. A need exists to improve these asthma self‐management skills within our current model of care, especially during the vulnerable postdischarge period. Aim To examine if the addition of a nurse‐led Asthma Care Transition Team (ACTT) compared with usual care alone (UC) (1) improves asthma control at 12 weeks posthospital discharge; the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Following title and abstract screening, 274 full texts were retrieved. A total of 126 RCTs involving 97 408 participants met our inclusion criteria (Figure 2). The study characteristics are presented in eAppendix 3 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following title and abstract screening, 274 full texts were retrieved. A total of 126 RCTs involving 97 408 participants met our inclusion criteria (Figure 2). The study characteristics are presented in eAppendix 3 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…Pooling data from 27 studies (34 direct comparisons) involving 13 039 participants, low-complexity (OR, 0.45; 95% CI, 0.30 to 0.66), medium-complexity (OR, 0.57; 95% CI, 0.35 to 0.91), and high-complexity (OR, 0.78; 95% CI, 0.62 to 0.98) interventions were associated decreased odds of readmission at 180 days compared with usual care (Figure 4). The P -score showed that low-complexity interventions ( P -Score = 94%) were most effective in reducing the 180-day readmission odds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations